Breakdown phenomenon dependences on the number and positions of threading dislocations in vertical p-n junction GaN diodes. (12th February 2021) - Ohta, Hiroshi; Asai, Naomi; Horikiri, Fumimasa; Narita, Yoshinobu; Yoshida, Takehiro; Mishima, Tomoyoshi
Abstract: The correlation between current-voltage ( I–V ) characteristics and threading dislocations was evaluated using p-n junction diodes on a high-quality GaN substrate with an average threading dislocation density (TDD) ≤ 4 × 10 5  cm −2 using the newly developed maskless 3D (M-3D) method. For the forward I–V characteristics, it was found that the "on" resistance ( R on ) increased as the number of dislocations in the diode increased. This result indicates that reducing the number of dislocations is effective in improving the forward I–V characteristics. On the other hand, for the reverse I–V characteristics, it was found that there was no clear correlation between the breakdown voltage ( V B ) and the number of dislocations. Also, the p-n diode's destruction point and dislocation position did not match in almost all of the measured p-n diodes. These results suggest that dislocation has very little effect on V B and the p-n diode destruction.